Stres kerja dan cybeloafing pada generasi Y dan Z: Peran usia dan status pernikahan sebagai boundary condition - Achmadi Achmadi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2021)
Using the transactional stress and border theory framework model, we explore the relationship between job stress and cyberloafing by placing biographies (age and marital status) as boundary conditions. An online questionnaire involved a total of 182 employees in this study. The analysis results using moderated hierarchical regression indicate that work stress has a positive and significant effect on cyberloafing behavior. In the moderation model, this study only proved that age was significant as a moderator in the relationship between job stress and cyberloafing, but not for marital status. In addition, age and marital status were not potential predictors of cyberloafing. Implications and suggestions are described in the article.